Origin of arc-like continental basalts: Implications for deep-Earth fluid cycling and tectonic discrimination - Wang, X.; Wilde, Simon; Xu, B.; Pang, C. (2015)
© 2015 Elsevier B.V. Continental basalts generally display enrichment of fluid-mobile elements and depletion of high-field-strength elements, similar to those that evolved in the subduction environment, but different from oceanic basalts. Based on the continental flood basalt database for six large igneous provinces, together with rift-related basalt data from the Basin and Range Province, this study aimed to test the validity of geochemical tectonic discrimination diagrams in distinguishing arc-like intra-continental basalts from arc basalts and to further investigate the role of deep-Earth water cycling in producing arc-like signatures in large-scale intra-continental basalts. Our evaluation shows that arc-like intra-continental basalts can be distinguished from arc basalts by integrating the following factors: (1) the FeO, MgO, and Al2O3 concentrations of the primary melt; (2) TiV, ZrZr/Y, ZrTi, and Ti/VZr/SmSr/Nd discrimination diagrams; (3) the coexistence of arc-like and OIB-like subtype basalts within the same province; (4) primitive mantle-normalized trace element distribution patterns. The similarity of enrichment in fluid-mobile elements (Ba, Rb, Sr, U, and K) between arc-like and true arc basalts suggests the importance of water flux melting in producing arc-like signatures in continental basalts. Experimentally determined liquid lines of descent (LLD) imply high magma water concentrations for continental flood basalts (CFBs) and the Basin and Range basalts. Furthermore, estimates based on the Al2O3-LLD method indicates 4.0-5.0wt% pre-eruptive magma H2O concentration for CFBs and the Basin and Range basalts. The tight relationships between H2O/Ce and Ba/La, Ba/Nb and Rb/Nb based on global arc basalt data were further used to estimate the primary H2O concentrations. With the exception of the Emeishan CFBs (mainly containing 4.0-5.6wt% H2O), all other CFBs investigated have similar estimated primary H2O contents, with values ranging from 1.0 to 2.0wt%. The estimated primary H2O content of the Basin and Range basalts is extremely high and up to 10.0wt%. Thus, this study demonstrates that water flux melting played an important role in the generation of many intra-continental igneous provinces. This new finding was further employed to investigate the tectonic setting of 320-270Ma basalts in Inner Mongolia, North China. Most basalts from three key rock units (i.e. Amushan, Benbatu, and Dashizhai formations) from the Central Asian Orogenic belt are classified as non-arc types. The estimated magma H2O concentrations suggest a strong link between H2O content and arc-like geochemical signatures. Together with established geological evidence, we proposed that these 320-270Ma basaltic rocks were most likely produced in a post-orogenic extensional environment facilitated by subducted slab-driven deep-Earth fluid cycling. We propose a mantle transition zone water-filtering model that links deep-Earth fluid cycling, large-scale intra-continental basaltic magmatism, and supercontinent cycles into a self-organized system.